Gods of deception : a novel - Cleveland, David Adams (Greenleaf Book Group Press, 2022)
At age ninety-five, Judge Edward Dimock, patriarch of his family and the man who defended accused Soviet spy Alger Hiss in the famous 1950 Cold War "trial of the century," is writing his memoir at his fabled Catskill retreat, Hermitage, with its glorious Italian Renaissance ceiling. Judge Dimock is consumed with doubts about the troubling secrets he's kept to himself for over fifty years--secrets that might change both American history and the lives of his entire family. Was his client guilty of spying for Stalin or not? And if guilty, did Hiss's crimes go far beyond his perjury conviction--a verdict that divided the country for a generation? Dimock enlists his grandson, George Altmann, a brilliant Princeton astrophysicist, in the quest for truth. Reluctantly, George finds himself drawn into the web of deceit that has ravaged his family, his curiosity sparked by a string of clues found in the Judge's unpublished memoir and in nine pencil sketches of accused Soviet agents pinned to an old corkboard in his grandfather's abandoned office. Even more dismaying, the drawings are by George's paternal grandfather and namesake, a once-famous painter who covered the Hiss trial as a courtroom artist for the Herald Tribune, only to die in uncertain circumstances in a fall from Woodstock's Fishkill Bridge on Christmas Eve, 1949. Many of the suspected spies also died from ambiguous falls (a KGB specialty) or disappeared behind the Iron Curtain--and were conveniently unable to testify in the Hiss trial. George begins to realize the immensity of what is at stake: deceptive entanglements that will indeed alter the accepted history of the Cold War--and how he understands his own unhappy Woodstock childhood, growing up in the shadow of a rumored suicide and the infidelities of an alcoholic father, a roadie with The Band.